Neural responses to advantageous and disadvantageous inequity - Fliessbach, Klaus; Phillipps, Courtney B.; Trautner, Peter; Schnabel, Marieke; Elger, Christian E.; Falk, Armin; Weber, Bernd (Frontiers in Human Neuroscience, 2012)
In this paper we study neural responses to inequitable distributions of rewards despite equal performance. We specifically focus on differences between advantageous (AI) and disadvantageous inequity (DI). AI and DI were realized in a hyperscanning fMRI experiment with pairs of subjects simultaneously performing a task in adjacent scanners and observing both subjects' rewards. Results showed i) hypoactivation of the ventral striatum under DI but not under AI; ii) inequity induced activation of medial and dorsolateral prefrontal regions, that were stronger under DI than AI; iii) correlations between subjective evaluations of DI and amygdala activity, and between AI evaluation and right ventrolateral prefrontal activity. Our study provides neurophysiological evidence for different cognitive processes that occur when exposed to DI and AI, respectively. Our data is compatible with the assumption that any form of inequity represents a norm violation, but that important differences between AI and DI emerge from an asymmetric involvement of status concerns.